Carrageenophyte Kappaphycus malesianus Inhibits Microglia-Mediated Neuroinflammation via Suppression of AKT/NF-κB and ERK Signaling Pathways - Lai, Nicole Jean Yean; Ngu, Ee Ling; Pang, Jun Rui; Wong, Kah Hui; Ardianto, Chrismawan; Long, Chiau Ming *; Lim, Siew Huah; Walvekar, Shweta Gangasa; Ayaz, Anwar; Yow, Yoon Yen * (MDPI, 2022)
Neuroinflammation is an inflammatory response in any part of the central nervous system triggered by the activation of microglia and astrocytes to produce proinflammatory cytokines in the brain. However, overproduction of proinflammatory cytokines further contributes to the development of neurodegenerative disorders. Red seaweed, Kappaphycus malesianus, is a predominant carrageenophyte commercially cultivated in Semporna, Sabah, Malaysia. It is an important source of raw material for kappa-carrageenan productions in the food, pharmaceutical and cosmetics industries. However, no studies have been conducted focusing on the antineuroinflammatory effects of K. malesianus. The aim of the present study was to investigate the effect of the antineuroinflammatory activity of K. malesianus extracts (ethyl acetate, ethanol and methanol) on lipopolysaccharide-stimulated BV2 microglia and the underlying mechanisms involved in the regulation of neuroinflammatory pathways. Extract with the most promising antineuroinflammatory activity was analyzed using liquid chromatography-mass spectrometry (LC-MS). Our results show that methanol extract has a convincing antineuroinflammatory effect by suppressing both AKT/NF-κB and ERK signaling pathways to inhibit the expression of all proinflammatory cytokines without causing a cytotoxicity effect. LC-MS analysis of methanol extract revealed two compounds: prosopinine and eplerenone. Our findings indicated that metabolites of K. malesianus are potent antineuroinflammatory agents with respect to prevention of neurological disorders.